Undesended testis: How extensive should the work up be? - Shera Altaf; Baba Aejaz; Gupta Shyam; Gupta Geetanjali; Sherwani Afak (Wolters Kluwer Medknow Publications, 2010)
Aim: The aim of this study was to highlight various anomalies associated with undescended testis and to determine how much work up is necessary for this condition. Material and Methods: The study was conducted in the department of Pediatric Surgery SKIMS Srinagar, Kashmir. All patients between 0-14 years of age who attended out patient department (OPD) from January 2002 to December 2003 with maldescent of testes were included in the study. Detailed relevant history and physical examination findings were recorded in all the cases. Baseline investigations were performed along with ultrasonography of the abdomen. In relevant cases other investigations like intravenous urography, micturating cystourethrography, CT scan and laparoscopy were performed as and when indicated. Results: A total of 250 cases of undescended testis were registered during this period. Maximum number of cases were in the age group of 5-10 years. In 130 (52%) cases the right testis was undescended while 75 (30%) had left sided undescended testis and 45 (18%) had bilateral undescended testis. Maldescended testis comprised 11% of the admissions. The majority of cases were having gestational age of 37 weeks or more. The associated anomalies picked up on investigations included duplication of upper urinary tract (3.2%), hydronephrosis and polycystic kidney (0.8% each), horseshoe kidney, ectopic kidney, crossed renal ectopia (0.4% each) Posterior urethral valves, Prune belly syndrome (0.4%) and spina bifida (0.4%). On detailed clinical examination of genitalia several abnormalities were picked which included hydrocele, hypospadias, hernia, chordee, micropenis and ambiguous genitalia. Conclusion: We recommend ultrasonography to be done in all cases of undescended testis in addition to a thorough history and physical examination. Intravenous pyelography, micturating cystourethrogram, CT scan and other investigations should be performed selectively based on history, physical examination or ultrasound findings.